Simplify. Express your answer using positive exponents.

(6k)(10k)

1 answer

To simplify the expression \((6k)(10k)\), follow these steps:

  1. Multiply the coefficients (the numerical parts): \[ 6 \times 10 = 60 \]

  2. Multiply the variable parts. Since both terms have the same variable \(k\), you can add the exponents (which are 1 here, since \(k = k^1\)): \[ k \times k = k^{1+1} = k^2 \]

  3. Combine the results from steps 1 and 2: \[ (6k)(10k) = 60k^2 \]

Thus, the simplified expression is: \[ \boxed{60k^2} \]